PENGARUH KOORDINASI TERHADAP EFEKTIVITAS PELAYANAN KAMPUNG KELUARGA BERENCANA KABUPATEN SUMEDANG - Ningrum, Dhesti Widya Nurhasanah (PERSPEKTIF, 2020)
The Family Planning Village Program in Sumedang Regency has been going on since 2016. Until now the formation of the Family Planning villages continues to form one KB village in each Sub-District so that the total number of Family Planning villages in Sumedang Regency is 27 Family Planning villages. The purpose of this study was to determine the effect of coordination on the effectiveness of family planning services in Sumedang Regency. The research method used is a quantitative method, which aims to describe and explain the existence of variables factually, as well as the relationship between variables with one another. Analysis of the data used includes the Calculation of Percentage, Calculation of Sperman Rank, Correlation Test, Significance Test and Determination Test Based on the results of the study found that the effect of coordination on the effectiveness of family planning services is 86%. So it can be concluded that coordination has a great influence on the effectiveness of services.